2021
DOI: 10.4103/jpgm.jpgm_1270_20
|View full text |Cite
|
Sign up to set email alerts
|

Association of atopic dermatitis with an increased risk of systemic lupus erythematosus

Abstract: Context: Previous studies on the association between atopic dermatitis (AD) and systemic lupus erythematosus (SLE) have yielded inconsistent results. Aims: To investigate the relationship between atopic dermatitis and systemic lupus erythematosus. Settings and Design: Systematic review and meta-analysis. Materials and Methods: A systematic review was conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Moreover, systematic review and metaanalysis studies showed that patients with underlying allergic rhinitis, asthma and atopic dermatitis all increased the risk of developing SLE. 22,23,24 Our study demonstrated that allergic diseases and SLE can coexist which contradict the Th1 /Th2 paradigm mechanistic theory of autoimmune diseases and allergic diseases. More evidence shows that active SLE, a primarily autoantibody-mediated autoimmune diseases is indeed characterized by decreased function of Th1 25 and hyperfunction of Th2 26 .…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, systematic review and metaanalysis studies showed that patients with underlying allergic rhinitis, asthma and atopic dermatitis all increased the risk of developing SLE. 22,23,24 Our study demonstrated that allergic diseases and SLE can coexist which contradict the Th1 /Th2 paradigm mechanistic theory of autoimmune diseases and allergic diseases. More evidence shows that active SLE, a primarily autoantibody-mediated autoimmune diseases is indeed characterized by decreased function of Th1 25 and hyperfunction of Th2 26 .…”
Section: Discussionmentioning
confidence: 60%
“…Allergic disease of conjunctiva (including allergic conjunctivitis, atopic keratoconjunctivitis, vernal keratoconjunctivitis and giant papillary conjunctivitis) are rarely diagnosed in SLE patients. In the studies, people with SLE were shown to be at increased risk of IgE-related allergic disorders and atopic diseases in comparison with control groups [ 23 ].…”
Section: Ophthalmic Manifestations Of Slementioning
confidence: 99%
“…SLE patients with active disease were found to have an increased level of IgE, identical to people with allergic diseases. As a result, it is probable that enhanced Th2 activity and IgE production seen in allergic diseases could lead to the development of SLE later in life (Ponvilawan et al, 2021).…”
Section: Subjects Characteristicsmentioning
confidence: 99%